2011
DOI: 10.1002/mc.20757
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of peroxisome proliferator‐activated receptor‐β/δ expression in colon cancer

Abstract: This study critically examined the role of PPARβ/δ in colon cancer models. Expression of PPARβ/δ mRNA and protein was lower and expression of CYCLIN D1 protein higher in human colon adenocarcinomas compared to matched non-transformed tissue. Similar results were observed in colon tumors from Apc+/Min-FCCC mice compared to control tissue. Dietary administration of sulindac to Apc+/Min-FCCC mice had no influence on expression of PPARβ/δ in normal colon tissue or colon tumors. Cleaved poly (ADP-ribose) polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 55 publications
8
63
0
Order By: Relevance
“…Moreover, knocking down expression of PPARD in TM4 mouse Sertoli cells mitigated these changes in expression of p27, cyclin D1, and cyclin D2. This is consistent with previous findings that ligand activation of PPARD suppresses cyclin D1 or increases p27 expression, causing inhibition of cell proliferation in cancer cells and primary keratinocytes (16,46,47). Furthermore, the present studies also demonstrated that ligand activation of PPARD alters expression of cell cycle regulators by modulating ERK activation in Sertoli cells in vivo and in vitro, consistent with previous studies (16, 48 -50).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, knocking down expression of PPARD in TM4 mouse Sertoli cells mitigated these changes in expression of p27, cyclin D1, and cyclin D2. This is consistent with previous findings that ligand activation of PPARD suppresses cyclin D1 or increases p27 expression, causing inhibition of cell proliferation in cancer cells and primary keratinocytes (16,46,47). Furthermore, the present studies also demonstrated that ligand activation of PPARD alters expression of cell cycle regulators by modulating ERK activation in Sertoli cells in vivo and in vitro, consistent with previous studies (16, 48 -50).…”
Section: Discussionsupporting
confidence: 93%
“…Several groups have reported that PPARD is upregulated in various human cancers, including colorectal, pancreatic, and lung cancer (5)(6)(7)(8)67), but others have reported contradictory findings (68). The present study's findings show that PPARD was upregulated in colorectal tumors in one of the largest cohorts of colorectal cancer patients yet studied.…”
Section: Discussionsupporting
confidence: 64%
“…Complex networks with other signaling pathways could provide a way to reconcile contradictory results from different systems (25,56,57). Interplay with ␤-catenin signaling might be reasonable, because of cancerspecific activation of ␤-catenin (50,58,59), association with PPAR-␦ overexpression (26,60,61), and cross-talk between TCF/␤-catenin signaling and PPAR expression and activity (62, 63). Here, we provide evidence that PPAR-␦ acts on the VEGFA gene along with ␤-catenin by regulating chromatin loops.…”
Section: Discussionmentioning
confidence: 99%